Features of risks assessment from the position of the behavioral economy - I. A. Kiseleva (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2018)
The problem of ensuring economic security of the enterprise is undoubtedly actual now as safety of the organization is directly connected with efficiency of functioning of the managing subject. In addition, in Russia there is an acute problem of unfair competition in the market, criminalization of certain segments that force enterprises to take certain measures. The analysis of risks of the enterprise allows to avoid not only essential material losses, but also irreparable damage and even bankruptcy. Economic security is an essential element of business operation and is a complex system of threat management inherent in business activities throughout the life cycle of the enterprise. It ensures achievement of business goals in conditions of competition and economic risk. The aim of the work is to study the main aspects of economic security of the enterprise in the Russian Federation. The object of the study of this work is the enterprise, and the subject – its economic security. The methods of cognition, retrospective and documentary analysis, economic and mathematical modeling, as well as synthesis, generalization, systematization were used as methods in the performance of the work. The efficiency of the enterprise depends not only on internal factors, but also on external: political, economic, geopolitical, environmental, social. The study of their complex influence on the functioning of an organization is the basis of ensuring the economic security of the company. In order to ensure the economic security of the organization, its stable operation and a stable position in the market, it is necessary to manage risks in order to minimize them, as well as mandatory measures to reduce the consequences and losses from risks.